Low-cost hybrid scaffolds based on polyurethane and gelatin - Rodrigues, Isabella Caroline Pereira; Woigt, Luiza Freire; Pereira, Karina Danielle [UNESP]; Luchessi, Augusto Ducati [UNESP]; Lopes, Eder Socrates Najar; Webster, Thomas J.; Gabriel, Lais Pellizzer (Elsevier B.V., 2020)
The production of scaffolds using a combination of synthetic and natural polymers has been widely studied for numerous tissue engineering applications, as it results in a material with superior properties, combining availability, processability, and the strength and resilience of synthetic polymers with the high biocompatibility of natural polymers. In the present study, fibrous membranes composed of polyurethane and gelatin were fabricated by rotary jet spinning and were posteriorly characterized for their morphological, chemical composition, thermal stability, hydrophilic properties as well as cell viability. Viscosity measurements were taken to achieve the critical concentration of the polymeric solution (9% wt/v), and the production of fibers at different rotational speeds (3000, 6000, 9000 and 12,000 rpm) was performed to evaluate the effect of rotational speed on fiber diameter and morphology, as observed in scanning electron microscopy analyses. Continuous and bead-free fibers were achieved at 6000 rpm with average diameter of 12.5 mu m. Chemical composition characterization showed the characteristic peaks of both polymers and the absence of the organic solvent, while the addition of gelatin did not affect the thermal stability of the membrane (up to 314 degrees C). Additionally, the water contact angle proved the membrane hydrophilic nature (81.3 degrees). Cell viability assays exhibited cytocompatibility with endothelial cells for 24, 48 and 72 h. The results demonstrate that the PU-Gel combination with the rotary jet spinning process is promising to obtain low-cost scaffolds with interesting properties for numerous tissue engineering applications, and, thus, should be further studied. (C) 2020 Published by Elsevier B.V.
Keywords: Implant; Membrane; Polymer; Tissue engineering; Protein; Rotary jet spinning